Design of Digital to Analog Voice Data Packet Conversion from Ethernet Protocol using FPGA - Barlian Henryranu Prasetio; Dahnial Syauqy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper describes a system that is designed to be able to receive packet voice signal using the Ethernet protocol in local networks using FPGA which was programmed decode the data packets. The digital data packets are then converted back into analog data that will be used to control another system. The design was implemented as four components consisting of frame starter unit, address matching unit, buffer unit and DAC processing unit. The system was designed on Xilinx development board using ISE design suite and simulated on ISIM. The test results showed that the system response was less than 40 ms. The result also showed that our proposed design only occupies 11% of number of slices and it also requires 5% of total IOBs on Xilinx Spartan 3-E.